Possessions and the Extended Self - Belk, Russell W. (Journal of Consumer Research, 1988)
Abstract Our possessions are a major contributor to and reflection of our identities. A variety of evidence is presented supporting this simple and compelling premise. Related streams of research are identified and drawn upon in developing this concept and implications are derived for consumer behavior. Because the construct of extended self involves consumer behavior rather than buyer behavior, it appears to be a much richer construct than previous formulations positing a relationship between self-concept and consumer brand choice.